Palaeoenvironmental and biostratigraphical implications of selected Floian and Dapingian (Ordovician) chitinozoans of the South China Palaeoplate. (28th September 2018) - Liang, Yan; Hints, Olle; Servais, Thomas; Luan, Xiao‐Cong; Nõlvak, Jaak; Tang, Peng; Wu, Rong‐Chang
Abstract : Chitinozoans are widespread microfossils in the Ordovician to Devonian strata. Although they have been widely adopted in biostratigraphy, their environmental preferences are rarely discussed. In this study, the palaeoecological distribution of four Floian and Dapingian key chitinozoans in six coeval stratigraphical units based on 13 sections from the South China Palaeoplate is discussed in detail, including Bursachitina maotaiensis (Chen 2009a), Bursachitina qianbeiensis (Chen 2009a), Conochitina decipiens and Sagenachitina dapingensis (Chen 2009b). It appears that B. maotaiensis and B. qianbeiensis preferred inner shelf environments and could spread to near‐shore and shallow outer shelf settings. C. decipiens mostly favoured inner shelf and shallow outer shelf environments. S. dapingensis had the widest environmental tolerance and was adapted to almost all environments, with the exception of the near‐shore area on the Yangtze Platform. Biostratigraphically, the four species have relatively well‐constrained ranges, and their first appearances provide good bases for regional correlations. The endemic B. maotaiensis and B. qianbeiensis can be good markers for the upper Floian, but their relatively narrow environmental preferences should be taken into account. S. dapingensis proves to be a good marker for the Dapingian in the South China Palaeoplate, except in the near‐shore areas. The globally distributed C. decipiens also has a biostratigraphical significance in most areas of the Yangtze Platform. Our study indicates that well‐documented environmental preferences of key species help to provide more reliable and practical biostratigraphical correlations.